Density and distribution of nipah (Nypa fruticans) on the western coast of Aceh, Indonesia - DEWI FITHRIA; HAIRUL BASRI; INDRA INDRA; ZAINAL A. MUCHLISIN (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Fithria D, Basri H, Indra I, Muchlisin ZA. 2024. Density and distribution of nipah (Nypa fruticans) on the western coast of Aceh, Indonesia. Biodiversitas 25: 2967-2973. Nypa fruticans Wurmb population on the west coast of Aceh, Indonesia, is under threat due to the frequent land conversion to plantations, aquaculture ponds, ports, and settlements, so reduced density and covered areas. Therefore, this study aims to analyze the density and distribution of nipah on the west coast of Aceh. The transect method was used with a size of 10x10m to count the number of trees, 5 x 5m to calculate the saplings, and 1 x 1m to count the seedlings. At each location, three sub-stations were determined purposively, namely (I) downstream near the mouth of the river, which is connected to sea waters, (II) towards upstream where nipah is still growing, as well as (III) between the upstream and downstream parts (mid area). The results showed that the density of nipah in Kuala Bubon for tree categories ranged from 12,700 to 14,800 ind. Ha-1, saplings 2,400 to 4,400 ind. Ha-1, and seedlings 110,000 to 140,000 ind. Ha-1. Meanwhile, in Kuala Tadu, the density of tree categories ranged from 1,900 to 3,800 ind. Ha-1, saplings 1,600 to 6,000 ind. Ha-1, and seedlings 60,000 to 80,000 ind. Ha-1. Moreover, the distribution index of Morishita in Kuala Bubon ranged from 0.02-0.72 and 0.05-0.58 in Kuala Tadu. The organic matter analysis in Kuala Bubon showed that C-organic ranged from 0.68-1.46%, N-total 0.09-0.12%, and P-total 1.55-4.1 mg/kg, while in Kuala Tadu, the values ranged from 0.66-3.63%, 0.05-0.15%, and 2.95-7.25 mg/kg respectively. Therefore, it was concluded that the density of nipah palm in both locations is very high and in good condition with uniformly distributed. However, the organic matter content at both locations was generally very low to low, except for C-organic at Kuala Tadu Station III and P element at Station II.